At odds? How European governments decided on public health restrictions during COVID-19. (April 2022) - Chae, S.; Kim, W.; Park, H.
Abstract: Objectives: This study aimed to understand how politics, economics, and public health restrictions affected each other during the COVID-19 pandemic. Methods: We use seemingly unrelated regressions on a monthly data set of government approval ratings, the stringency index, the time-dependent reproduction number (R), and unemployment, allowing the residuals in each regression to be correlated with each other. We also conduct sensitivity tests using weekly data and the growth in polls. Results: The study covers 27 European countries from April 2020 to April 2021. A unit increase in the R and COVID-19 cases per million increases the stringency index by 23.742 and 4.207, respectively; a unit increase in stringency boosts the incumbent's popularity by 0.384; the poll positively affects the stringency index; stringency has negative effects on the R; and the poll and stringency index have opposite effects on unemployment. Conclusion: Political and economic pressures did not hinder the government from introducing stronger measures.